2019
DOI: 10.1080/19476337.2019.1586776
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of vanilla juice and vanillin against Alternaria alternata

Abstract: Vanilla juice has been shown empirically to have antifungal activity against some fungal strains; however, there are no activity reported against Alternaria genre. In this work, the chemical profile of vanilla juice was obtained and its antifungal activity against fungal strains from the family Pleosporaceae, isolated from sorghum-and barley-diseased plants, was tested. The strains were identified as Alternaria alternata by their molecular and morphological characteristics. The vanilla juice characterization f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…In addition, Romero-Cortes et al evaluated the antifungal activity of vanillin against Alternaria alternata isolated from sorghum and barley. The vanillin showed a fungicidal effect in a dose-dependent manner; moreover, doses lower than 750 mg/L of vanillin reduced the fungal growth, increasing the lag phase from 50 to 112 h [44].…”
Section: Phenolic Acids Produced By L Plantarum Sppmentioning
confidence: 94%
“…In addition, Romero-Cortes et al evaluated the antifungal activity of vanillin against Alternaria alternata isolated from sorghum and barley. The vanillin showed a fungicidal effect in a dose-dependent manner; moreover, doses lower than 750 mg/L of vanillin reduced the fungal growth, increasing the lag phase from 50 to 112 h [44].…”
Section: Phenolic Acids Produced By L Plantarum Sppmentioning
confidence: 94%
“…It is found that vanillin can impede the growth of such fungal pathogens. For instance, vanillin (250 mg/L) decreased the growth of Alternaria strains, suggesting its fungistatic behaviour where the lag time of fungal life cycle was increased from initial 50 h to 112 h and also inhibition of mycelial growth of up to 37.5% was observed (Romero-Cortes et al 2019). Antifungal activity of vanillin and its 33 variants were tested against Cryptococcus neoformans which is the causative agent of cryoptococcal meningitis (Kim et al 2014).…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Hexanal, 2‐methoxy‐4‐vinylphenol and octanal are the major compounds that contribute to the aromatic intensity of rice and have shown antioxidant, anti‐inflammatory, antimicrobial and anti‐diabetes properties (Jeong et al ., 2011; Liu et al ., 2012). Moreover, some volatile compounds identified from coloured rice, such as vanillin, vanillyl alcohol, guaiacol and 2‐pentylfuran, have also been reported to show antioxidant, anti‐inflammatory, and antifungal activity (Jung et al ., 2008; Azadfar et al ., 2015; Romero‐Cortes et al ., 2019). Furthermore, some of these volatile compounds have shown cosmeceutical potential (anti‐tyrosinase activity) (Razak et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%